Prevalence and Associated Factors of Needlestick and Sharps Injuries among Healthcare Workers in Saudi Arabia: A Systematic Review and Meta-analysis - Mohammed A. Alsuliman (The Open Public Health Journal, 2026)
Background Needlestick and sharps injuries (NSIs) are a major occupational hazard for healthcare workers (HCWs) in Saudi Arabia, yet national-level data on their prevalence and associated factors remain limited. Objectives To estimate the pooled prevalence of NSIs among HCWs in Saudi Arabia and identify associated factors. Methods This systematic review and meta-analysis followed PRISMA 2020. Cross-sectional studies reporting NSI prevalence among HCWs in Saudi Arabia were retrieved from PubMed, EBSCOhost, Web of Science, and Google Scholar, and appraised with the JBI prevalence checklist. Prevalence was pooled using a random-effects Freeman-Tukey model, with a generalized linear mixed model as a sensitivity analysis and a 95% prediction interval. Subgroup analyses and meta-regression explored heterogeneity. Results Twenty-five studies (7,635 HCWs) were included. The pooled prevalence was 35.5% (95% CI: 23.9-48.0), with high heterogeneity (I 2 = 98.7%) and a prediction interval of 0-93.8%, indicating no single underlying rate; a generalized linear mixed model gave 34.6%. Prevalence was higher in males (48.2%) than females (32.7%) and in the Eastern region (83.6%, k = 2). Needles caused 76% of injuries, and about 35% were unreported. Discussion The pooled estimate should be interpreted as the center of a wide distribution rather than a national rate, given the persistent heterogeneity within subgroups. Estimates from single or few studies are exploratory. High underreporting and the predominance of needle injuries are modifiable prevention targets. Conclusion NSIs remain common but highly variable among Saudi HCWs. Standardized surveillance, safety-engineered devices, and targeted training are needed, alongside methodologically consistent prospective studies.